2022
DOI: 10.11591/ijphs.v11i3.21362
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, perception, and behavior of pregnant women against COVID-19 transmission

Abstract: The outbreak of COVID-19 had a significant impact in terms of economic and social health. Assessing the community's knowledge regarding the transmission of COVID-19 is essential to specify the target of promoting and preventive actions. Therefore, the research aimed to assess pregnant women's knowledge, perception, and behavior against COVID-19 transmission. The research is a quantitative cross-sectional study. Pregnant women who received antenatal care at PKU Muhammadiyah Mamajang Makassar Hospital were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…In line with research conducted by Nadifa et al (2021) which shows good COVID-19 prevention behavior in pregnant women at 89.0%. Compliance with carrying out health protocols for pregnant women at the PKU Muhammadiyah Mamajang Makassar hospital showed higher results than this study, namely 97.7% (Nurdin et al, 2022). Research conducted in Malaysia on pregnant women showed the same results where compliance with washing hands was 98.8% and using masks was 96.1% (Aly et al, 2021).…”
Section: Resultssupporting
confidence: 38%
“…In line with research conducted by Nadifa et al (2021) which shows good COVID-19 prevention behavior in pregnant women at 89.0%. Compliance with carrying out health protocols for pregnant women at the PKU Muhammadiyah Mamajang Makassar hospital showed higher results than this study, namely 97.7% (Nurdin et al, 2022). Research conducted in Malaysia on pregnant women showed the same results where compliance with washing hands was 98.8% and using masks was 96.1% (Aly et al, 2021).…”
Section: Resultssupporting
confidence: 38%
“…The results obtained in this study are supported by research conducted by Tao et al (2021) using the cross-sectional method with a sample size of 1392, which obtained a p-value of 0.01, <0.05 which showed that the higher the knowledge of pregnant women regarding COVID-19 vaccination, the higher they wanted to receive the vaccination (Tao et al, 2021). In another study conducted by Nurdin et al (2021) using the cross-sectional method on 220 pregnant women, there was found a relationship between the behavior of pregnant women and the level of knowledge of respondents about the transmission of COVID-19 with a p-value *0.001<0.05 (Nurdin et al, 2022). The results obtained by Mose and Yeshaneh (2021) through a cross-sectional study found that among 396 pregnant women, those with a good level of knowledge regarding COVID-19 and how to prevent it are easier to take the COVID-19 vaccine compared to pregnant women with lesser knowledge (Mose & Yeshaneh, 2021).…”
Section: Correlation Between Knowledge and Pregnant Women's Practice ...mentioning
confidence: 87%
“…According to Nur, et al, 15 using the Preferred Reporting Items for Systematic Review (PRISMA) systematic method, it was found that the higher the level of knowledge, the higher the acceptance rate of the Covid-19 vaccine, conversely, the lower the knowledge, the lower the interest of individuals to do the Covid-19 vaccine. According to Nurdin, et al 23 it was revealed that there was also a relationship between the behavior of pregnant women and the level of knowledge of respondents about the transmission of Covid-19 with a p-value of 0.001 <0.05. Concerning parents and children, namely parents who make decisions rather than a child's actions including the Covid-19 vaccination in this study is in line with the literature according to Bono, et al 24 that good parental knowledge about Covid-19 is associated with acceptance of the Covid-19 vaccination with a p-value of 0.001 <0.05.…”
Section: Discussionmentioning
confidence: 99%